Experiences of newly qualified dentists in delivering oral health advice to parents/caregivers of young children—challenges and solutions - Rutter, Lucy; Duara, Raginie; Vinall-Collier, Karen A.; Owen, Jenny; Haley, Isabelle; Gray-Burrows, Kara A.; Hearnshaw, Simon; Marshman, Zoe; Day, Peter F. (Frontiers in Oral Health, 2023)
Introduction A key skill for dental professionals to master is their ability to have effective preventive oral health conversations. On qualifying, UK dentists undertake a one-year foundation training programme in general practice. This study explored with Foundation Dentists, the barriers and facilitators to undertaking oral health conversations with parents/caregivers and their children, aged 0–11 years old. Materials and methods Approximately 100 Foundation Dentists from the Yorkshire and Humber region attended a series of focus groups. They discussed how they and their wider dental team undertake oral health conversations with parents/caregivers of young children, aged 0–11 years old. The data was analysed using thematic analysis. Results Five themes were identified as barriers and facilitators to providing oral health advice: (1) Lack of knowledge around parenting skills and child development; (2) Parental receptivity; (3) Motivation for changing behaviours; (4) Information content and inconsistency; and (5) Current National Health Service (NHS) structures of general dental practice. Discussion A multi-faceted approach is needed to develop the training of Foundation Dentists to undertake preventive oral health conversations with parents/caregivers and children. Such an approach has the potential to improve the patient-practitioner relationship and increase effective behaviour change conversations taking place in general dental care, thus improving children's oral health.